Mapping extent of agroforestry area through remote sensing: Issues, estimates and methodology - Rizvi, R.H.; Dhyani, S.K.; Newaj, Ram; Saxena, A.; Karmakar, P.S. (Indian Journal of Agroforestry, 2020)
Various forms of agroforestry practice are prevalent in different agro-climatic regions of India. They occupy sizeable area in the country that is yet to be estimated accurately. Geospatial technologies have the potential for mapping and delineating agroforestry area for large geographical extent whether region or country. Since agroforestry comprises of trees, crops, grasses and many more components, so there are some problems in mapping which are highlighted in this article. Besides this, methodology has been proposed for mapping agroforestry area using medium resolution (LISS III) remote sensing data. Area under agroforestry in Ludhiana district was estimated using medium resolution (LISS III) and high resolution (LISS IV) data and pixel based classification method.By this method, area under agroforestry was estimated to 14.87, 5.56 per cent in case of LISS IV and LISS III data, respectively. Sub-pixel classifier was also applied on medium resolution (LISS III) data and the results were compared. In this case, area under agroforestry was estimated to be 14.91 per cent, which is almost same as that of result obtained with LISS IV data. Thus, result obtained by sub-pixel classification of medium resolution data are as good as obtained by pixel based classification of high resolution data. Hence, proposed methodology may be used for accurate assessment of area under agroforestry in India.Â